Giant intramuscular lipoma of the tongue: a case report and literature review - Colella, Giuseppe (BioMed Central, 2009)
We herein report a rare case of giant intramuscular lipoma of the tongue. A 75-year-old Italian male presented at our department with a large tumor at the tip of the tongue that had been present for over 30 years. Clinical examination revealed a yellowish lesion, measuring 10 cm in maximum diameter, protruding from lingual surface. Histological examination showed an unencapsulated lipomatous tumor composed of mature adipocytes, uniform in size and shape, diffusely infiltrating striated muscle fibers of the tongue. The patient is well with no local recurrence after a 15-month follow-up period.